LIPASE ACTIVITIY OF MIXTURE OF FERMENTED AVOCADO (Persea americana), BANANA (Moses paradisiaca) AND SNAKEFRUIT (Salacca zalacca) - Yazid, Edy Agustian (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Fermentation is one of the bioconversion processes to produce anaerobic microbes which are beneficial and can produce enzymes. One of the enzymes that can be produced is lipase. Mixed fruit fermentation is an effort to produce lipase that can be done simply. The purpose of this research is to know the activity of lipase enzyme from mixture of fermented avocado fruit (Persea americana), bananas (Musa paradisiaca) and snakefruit (Salacca zalacca). Lipase enzyme activity is tested by measuring of free fatty acid (FFA) content obtained from olive oil hydrolysis process by lipase enzyme. The results showed the highest activity obtained 17.425 U/ml and the percentage of FFA produced was 12.94%. The highest activity of lipase enzyme was obtained at 450C and pH 6.5. From this research can be concluded that the fermentation of the mixture of avocado, bananas and snakefruit can produce lipase enzyme that has relatively high activity.Â Keywords: Enzyme Activity, Fruits, Fermentation, Lipase.Â